2008
DOI: 10.1002/marc.200700697
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Micellization of Diblock Copolymer Mixtures Mediated by Hydrogen Bonding for the Observation of Separated Coil and Chain Aggregation in Common Solvents

Abstract: This paper describes a new approach towards preparing self‐assembled hydrogen‐bonded complexes that have vesicle and patched spherical structures from two species of block copolymer in non‐selective solvents. The assembly of vesicles from the intermolecular complex formed after mixing polystyrene‐block‐poly(4‐vinyl phenol) (PS‐b‐PVPh) with poly(methyl methacrylate)‐block‐poly(4‐vinylpyridine) (PMMA‐b‐P4VP) in tetrahydrofuran (THF) is driven by strong hydrogen bonding between the complementary binding sites on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…These types of particles can also be made with mixtures of different block copolymers and variation of the ratio of molecules in the assembly mixture. Moreover, without being covalently linked in the same molecular backbone, components in the mixture are responsive to various external stimuli such as solvent exchange, [ 40 ] changes in temperature, pH, [ 41 ] ionic strength, [ 23 ] and assembly kinetics. [ 26 ] Also, the components are dynamic enough to demix internally into compartments of diverse sizes and geometries depending on the type and amount of block copolymers in the original mixture.…”
Section: Resultsmentioning
confidence: 99%
“…These types of particles can also be made with mixtures of different block copolymers and variation of the ratio of molecules in the assembly mixture. Moreover, without being covalently linked in the same molecular backbone, components in the mixture are responsive to various external stimuli such as solvent exchange, [ 40 ] changes in temperature, pH, [ 41 ] ionic strength, [ 23 ] and assembly kinetics. [ 26 ] Also, the components are dynamic enough to demix internally into compartments of diverse sizes and geometries depending on the type and amount of block copolymers in the original mixture.…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49][50]) or corona-forming blocks (see for example Refs. [51][52][53]). Finally, we would like to point out that self-consistent field calculations on bimodal (bidisperse) brushes (polymer brushes consisting of two types of polymers differing only in size; that is, identical in chemical composition) have demonstrated that patchy brushes can arise merely as a result of a distinct difference in polymer block length [54]; that is, without any chemical incompatibility as all polymer chains were of identical chemical composition.…”
Section: Corona Structurementioning
confidence: 99%
“…The research done so far mostly involves the micellization of block copolymers in solvents other than pure aqueous medium [87][88][89] or the use of copolymers (in block form or otherwise) with and without mixing with homopolymers in organic solvents [16,90,91]. Copolymers and homopolymers were also mixed in organic solvents to produce vesicles mediated by the hydrogenbonding [91][92][93][94]. These mixed micelle systems were not customized for drug delivery purposes but merely studied to explore their behaviors in different milieus.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
“…FTIR spectra are useful in indicating hydrogen bonds between specific hydrogen bond acceptors and donors in the different blocks of the copolymers when there is a shift of peak frequency of bands to a lower wavenumber. For example, the hydrogen bonds between polystyrene-block-poly(4-vinyl phenol) (PS-b-PVPh) and poly(methylmethacrylate)-block-poly(4-vinylpyridine) (PMMA-b-P4VP) were studied by FTIR in THF and DMF [91,94]. Information extracted from the spectra such as the difference in the shift of the wavenumbers of hydroxyl bands of P4VP after mixing with PS-b-PVPh then alluded to the difference in strength of the H-bonding between the PVPh and P4VP blocks in different solvents.…”
Section: Hydrogen Bondingmentioning
confidence: 99%